Social media use: A review of innovation management practices - Muninger, Marie-Isabelle; Mahr, Dominik; Hammedi, Wafa (Journal of business research, 2022)
The use of social media for innovation requires firms to manage rapid information transfers, big data, and multiway communication. Yet managers lack clear insights on the way social media should be managed and current literature is dispersed across various research streams. In this article, the authors aim to develop a better understanding of how social media use should be leveraged for innovation. To achieve this objective, they build a systematic review of evidence from 177 scientific articles across four key management disciplines. They analyze research perspectives and conceptualizations of social media use for innovation and provide a framework of the drivers, contingencies and outcomes related to this topic. Next, they attempt to identify what is currently known about social media use for innovation. Last, they suggest critical areas for future inquiry on this important subject.